Effectiveness of The Board of Directors and Company Performance: Corporate Governance Perspective in Indonesia - Pratiwi, Ririh Dian; Chariri, Anis (Jurnal Penelitian Ekonomi dan Bisnis, 2021)
The purpose of this study was to determine the effect of board size, board independence, and board activity on company performance from a corporate governance perspective. This study uses a quantitative approach. IDX issuers in the manufacturing sector registered in 2017-2018 are the research population. The samples were obtained using the purposive sampling method. Based on the criteria, the samples in this study were 146 companies. This study uses multiple linear regression analysis. This study found that board size has a negative effect on ROA, but has an effect on and is positively correlated with ROE. Board independence has a positive effect on the achievement of company ROA and ROE. While the third variable, namely board activity does not affect the achievement of ROA and ROE of the company. Based on the limitations, further research is expected to be able to explore other factors that are relevant in influencing company performance during and after the COVID 19 pandemic, for example, namely external factors. Keywords: Board of Directors, Corporate Governance, Company performance